Tamoxifen Initiation After Ductal Carcinoma In Situ. (14th January 2016) - Nichols, Hazel B.; Bowles, Erin J.A.; Islam, Jessica; Madziwa, Lawrence; Stürmer, Til; Tran, Diem-Thy; Buist, Diana S.M.
Abstract: Background: Endocrine therapy initiation after ductal carcinoma in situ (DCIS) is highly variable and largely unexplained. National guidelines recommend considering tamoxifen for women with estrogen receptor-positive (ER+) DCIS or who undergo excision alone. We evaluated endocrine therapy use after DCIS over a 15-year period in an integrated health care setting to identify factors related to initiation. Methods: Female Group Health Cooperative enrollees ages 18–89 years with a DCIS diagnosis during 1996–2011 were eligible for inclusion. Endocrine therapy was identified through pharmacy records. Tumor and treatment information were from tumor registry reports; demographics and other risk factors were from questionnaires and electronic medical records. Relative risks (RRs) and 95% confidence intervals (CIs) for endocrine therapy initiation were calculated using multivariable generalized linear models. Results: We identified 727 women with a DCIS diagnosis, including 163 (22%) who initiated endocrine therapy (149 tamoxifen, 14 aromatase inhibitor). Younger women were more likely to initiate endocrine therapy (RR 1.69; 95% CI 1.16–2.46 for ages 45–54 vs. 65–74 years). Compared with breast-conserving surgery (BCS) with radiation, women who had BCS alone (RR 0.46; 95% CI 0.25–0.84) or mastectomy (RR 0.54; 95% CI 0.39–0.75) were less likely to use endocrine therapy. ER testing increased from 4% of DCIS cases in 2001 to 71% in 2011; however, endocrine therapy initiation decreased from 58% of ER+ DCIS in 2001–2005 to 37% in 2009–2011. Conclusion: Increasing ER testing since 2001 has not corresponded to parallel increases in endocrine therapy initiation. Age, surgery, and radiation were the primary factors associated with initiation. Abstract : In this study, which evaluated endocrine therapy use after ductal carcinoma in situ (DCIS) over a 15-year period, 163 of 727 women with a DCIS diagnosis (22%) initiated endocrine therapy. Age, surgery, and radiation were the primary factors in initiation, but increased estrogen receptor testing has not resulted in corresponding increases in endocrine therapy.